2021
DOI: 10.1371/journal.pone.0262088
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of critical thinking in the Middle East: Evaluating the effectiveness of special courses interventions

Abstract: Critical thinking is a requisite skill for college success, employability, and conducive active civic participation. Empirical studies have noted to the low achievement of Arab students on critical thinking assessments. Insufficient endeavors have attempted to propose effective interventions enhancing critical thinking abilities among Arab students. The current analysis provides a preliminary overview of a special course designed to improve critical thinking skills among Arab college students. Results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…The research findings showed that the students' knowledge 5 Tedjo et al The Relationship between English Language Proficiency and Logical Thinking Skills of logical arithmetic and their knowledge of technology did not correlate significantly. In another recent study, Yousef (2021) has made a preliminary overview on the improvement of Arab college students' critical thinking skills. The participants joining the Mathematic course were assigned a project requiring them to perform a series of skills, one of which is by using Microsoft Excel to prepare personal budgets.…”
Section: Logical Thinking In Using Microsoft Excelmentioning
confidence: 99%
“…The research findings showed that the students' knowledge 5 Tedjo et al The Relationship between English Language Proficiency and Logical Thinking Skills of logical arithmetic and their knowledge of technology did not correlate significantly. In another recent study, Yousef (2021) has made a preliminary overview on the improvement of Arab college students' critical thinking skills. The participants joining the Mathematic course were assigned a project requiring them to perform a series of skills, one of which is by using Microsoft Excel to prepare personal budgets.…”
Section: Logical Thinking In Using Microsoft Excelmentioning
confidence: 99%
“…In addition, critical thinking skills encourage students to think in detail in finding a solution (Haryati et al, 2022;Dakabesi et al, 2019). Thinking skills encourage students to provide odoriferous ideas in solving a problem (Yousef, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Critical thinking skills are skills that guide students to think analytically and systematically in solving a problem (Chowning et al, 2012;Snyder & Wiles, 2015;Elfira et al, 2023;Yousef, 2021). Critical thinking skills help students to think at a higher level in learning (Ichsan et al, 2023;Ayuningrum et al, 2015;Anindyta & Suwarjo, 2014).…”
Section: Introductionmentioning
confidence: 99%